Enhancing Personalized Learning: The Impact of Artificial Intelligence in Education - Muhammad Zailani Iman; Alfian Airlangga Asis; Aynu Uzma Zein Rahma (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This research explores the transformative impact of artificial intelligence (AI) on personalized learning in educational settings. As traditional teaching methods struggle to cater to the diverse needs of students, AI offers innovative solutions that can tailor educational experiences to individual learning styles, preferences, and paces. This study investigates the various applications of AI technologies, including intelligent tutoring systems, adaptive learning platforms, and data-driven insights, to enhance personalized learning outcomes. By employing a mixed-methods approach that combines quantitative analysis of academic performance metrics with qualitative feedback from students and educators, the research aims to assess the effectiveness of AI-driven personalized learning initiatives. The findings reveal that AI not only improves student engagement and motivation but also facilitates differentiated instruction that addresses learning gaps and strengths. Additionally, the study identifies challenges such as data privacy concerns and the need for professional development for educators to effectively integrate AI solutions into their teaching practices. Ultimately, this research contributes to the ongoing discourse on the role of AI in education, offering actionable recommendations for educators and policymakers to optimize personalized learning experiences for all students.